Pemberian Ekstrak Sargassum sp. melalui Pakan Komersil Terhadap Nilai Hematokrit dan Diferensial Leukosit pada Ikan Bawal Bintang Trachinotus blochii - Azminar Yuliana Yuli; Aminatul Zahra; Rika Wulandari (Program Studi Budidaya Perairan Universitas Maritim Raja Ali Haji, 2021)
Sargassum sp. is a natural ingredient that can be used to improve the health status of fish. This study aims to test the extract concentration of Sargassum sp. which is mixed into commercial feed against the hematological profile of star pomfret. This research was conducted in September - November 2020. The process of extraction and toxicity tests was carried out at the Marine Chemistry Laboratory FIKP, then in-vivo tests were carried out in Madong Village, Kampung Bugis Village. The fish blood profiles were analyzed at the Marine Biotechnology Laboratory FIKP. The research method used was experimental using a completely randomized design (CRD) with 4 treatments and 3 replications, namely control (0 ppm extract of Sargassum sp. + feed), treatment A (38 ppm extract of Sargassum sp. + feed), treatment B (58 ppm extract of Sargassum sp. + feed), and treatment C (78 ppm extract of Sargassum sp. + feed). The results showed that the highest hematocrit value was 54.65%, the highest lymphocyte percentage was 87.67%, the highest monocyte percentage was 6.00%, and the highest neutrophil percentage was 7.33%. Provision of SargassumExtract sp.. at a dose of 58 ppm through commercial feed has an effect on the hematocrit value and the percentage of lymphocytes but does not have an effect on the percentage of monocytes and neutrophils in pomfret fish